The Antibiotic Bacitracin Protects Human Intestinal Epithelial Cells and Stem Cell-Derived Intestinal Organoids from Clostridium difficile Toxin TcdB - Ziyu Zhu; Leonie Schnell; Bastian Müller; Martin Müller; Panagiotis Papatheodorou; Holger Barth (Hindawi Limited, 2019)
Bacitracin is an established antibiotic for local application and inhibits the cell wall synthesis of Gram-positive bacteria. Recently, we discovered a completely different mode of action of bacitracin and reported that this drug protects human cells from intoxication by a variety of medically relevant bacterial protein toxins including CDT, the binary actin ADP-ribosylating toxin of Clostridium (C.) difficile. Bacitracin prevents the transport of CDT into the cytosol of target cells, most likely by inhibiting the transport function of the binding subunit of this toxin. Here, we tested the effect of bacitracin towards TcdB, a major virulence factor of C. difficile contributing to severe C. difficile-associated diseases (CDAD) including pseudomembranous colitis. Bacitracin protected stem cell-derived human intestinal organoids as well as human gut epithelial cells from intoxication with TcdB. Moreover, it prevented the TcdB-induced disruption of epithelia formed by gut epithelium cells in vitro and maintained the barrier function as detected by measuring transepithelial electrical resistance (TEER). In the presence of bacitracin, TcdB was not able reach its substrate Rac1 in the cytosol of human epithelial cells, most likely because its pH-dependent transport across cell membranes into the cytosol is decreased by bacitracin. In conclusion, in addition to its direct antibiotic activity against C. difficile and its inhibitory effect towards the toxin CDT, bacitracin neutralizes the exotoxin TcdB of this important pathogenic bacterium.